NUTRITIONAL ASSESSMENT IN CHILDREN FROM AN EDUCATIONAL INSTITUTION. THE SCHOOL THAT FEEDS? - Olbrich Neto, Jaime (2010)
We live in a nutritional transition from malnutrition to obesity. Monitoring children´s nutritional status is important. Social factors and economic background could determine the increased prevalence of obesity, even among the poor, at risk for chronic diseases.The school snack can be an obstacle to quality food being bought at the cafeteria, prepared at home, or even served as school meals. This study sought to evaluate the nutritional status of children in a school where there is no cafeteria, only meals provided by the public service. 386 children, aged 4 to 11 years, from a charity school were evaluated by sex, age, weight, height, index body mass, skinfolds, cholesterol, triglycerides, menu, food weight, number of times they were served, and caloric value. Out of these, 52% were boys. There was a higher proportion of overweight or obese boys (p = 0.04). We have found higher values of total cholesterol among obese and overweight children (p = 0.000); with expressive difference if compared to the caloric values of the meals served and the amount offered according to the children age. More than 40% of the children requested and received food more than once, at the same period of the day. There are more overweight and obesity than malnutrition in this population, and school meals may encourage healthy eating habits, but is lacking fruits and vegetables.